INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR UPTB SAMSAT KABUPATEN MERANGIN - Supriyati; Wahid, Darham; Asman, Muhammad; Herawati; Novriansyah, Yudhi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
This research aims to measure the level of public satisfaction with services at the UPTB SAMSAT in Merangin Regency based on the Regulation of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. The type of research used is Descriptive with a quantitative data analysis approach. The sample consists of the community members who made vehicle tax payments at the UPTB Samsat Office in Merangin Regency from January to March 2025, totaling 100 people using the incidental sampling technique. The results of the research on the Level of Community Satisfaction with the Services of the UPTB Samsat Office in Merangin Regency have been conducted well, where the community satisfaction index was obtained from 9 indicators with an Indeks Kepuasan Masyarakat ( conversion value = Σ Weighted NRR × 20 Public Satisfaction Index (PSI) Conversion Value = 4.082 × 20 = 81.64) service quality "B," which means "Good." Based on the indicators of public satisfaction with SAMSAT services, the indicator with the highest public satisfaction index (PSI) is the Behavior of the Staff = 4.21 with a conversion value of 84.2, categorized as "A" Very Good. Meanwhile, the indicator with the lowest value is the Completion Time = 4 with a conversion value of 80, categorized as "B" Good.